2013
DOI: 10.1515/jlt-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Outer vs. Inner Reverberations: Verbal Auditory Imagery and Meaning-Making in Literary Narrative

Abstract: It is generally acknowledged that verbal auditory imagery, the reader's sense of hearing the words on a page, matters in the silent reading of poetry. Verbal auditory imagery (VAI) in the silent reading of narrative prose, on the other hand, is mostly neglected by literary and other theorists. This is a first attempt to provide a systematic theoretical account of the felt qualities and underlying cognitive mechanics of VAI, based on convergent evidence from the experimental cognitive sciences, psycholinguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition to imaging the environments and situations rendered in a story, readers readily engage in conjuring so-called verbal imagery. Verbal imagery does not represent nonverbal entities but linguistic structures: a word, a rhyme, a verse, a sentence, and so forth (Kuzmičová, 2013). These structures are then experienced as if covertly pronounced by the reader herself, or as if heard pronounced by someone else (a character or narrator).…”
Section: Situating Narrative 14mentioning
confidence: 99%
“…In addition to imaging the environments and situations rendered in a story, readers readily engage in conjuring so-called verbal imagery. Verbal imagery does not represent nonverbal entities but linguistic structures: a word, a rhyme, a verse, a sentence, and so forth (Kuzmičová, 2013). These structures are then experienced as if covertly pronounced by the reader herself, or as if heard pronounced by someone else (a character or narrator).…”
Section: Situating Narrative 14mentioning
confidence: 99%
“…Another perspective-also provided by cognitive literary studies-is to consider how fictional minds may be differently represented from the outside and the inside. Kuzmičová (2013), for example, has suggested that we experience characters' speech in literary texts as either "outer reverberations" (when we read, as vicarious listeners, about a character overtly speaking) and "inner reverberations" (when we voice a character's words within his or her perspective). In parallel, Caracciolo (2014) has highlighted the contrast between attributing intentions to characters and the direct, inner enactment of a character's thoughts and fictional consciousnesses more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…This is sometimes conceptualized either as inner speech – namely, the various ways in which people talk to themselves ( Alderson-Day & Fernyhough, 2015 ) – or more broadly in terms of auditory imagery, i.e. purposefully imagining the qualities of characters’ or narrators’ voices ( Hubbard, 2010 , Kuzmičová, 2013 ). Evidence of inner speech involvement comes from psycholinguistic studies on reading: when we read, phonologically longer stimuli take longer to read than shorter stimuli of the same orthographic length ( Abramson and Goldinger, 1997 , Smith et al, 1992 ), while acoustic properties of one’s own voice, such as accent, can affect our expectation of rhyme and prosody (e.g., Filik & Barber, 2011 ).…”
Section: Introductionmentioning
confidence: 99%